Taxonomy, Autecology And Distribution Of Najas Marina L. (Najadaceae) In Bangladesh (Bangladesh Journal of Plant Taxonomy, 2022)
Detailed taxonomic description of Najas marina L. including information on flowering and fruiting time, autecology, and distribution in Bangladesh are provided. The diagnostic characters with illustrations and behavioural patterns of different habitats are also provided. Presence of Najas marina in Joydia baor indicates that the water quality of this baor is fairly good and minor human interference of the habitats.Bangladesh J. Plant Taxon. 29(2): 183-191, 2022 (December)